Responsive feeding practices among Arabic and Mongolian speaking migrant mothers in Australia: A qualitative study - Danielle Jawad; Li Ming Wen; Louise Baur; Chris Rissel; Seema Mihrshahi; Sarah Taki (Maternal and Child Nutrition)
Abstract Establishing healthy feeding habits during infancy is crucial for optimal growth. However, certain parental feeding and cultural practices might hinder the development of children's healthy eating behaviours. This research explored responsive feeding practices among migrant mothers in Australia. Semi‐structured telephone interviews were conducted in their native language with 20 Arabic and 20 Mongolian‐speaking migrant mothers with children under 2 years old or currently pregnant. Thematic analysis was conducted using the framework method. Both cultural groups followed a variety of feeding practices, including on demand responsive feeding or structured schedules. Arabic‐speaking mothers tended to demonstrate responsive feeding practices more frequently than Mongolian‐speaking mothers, except for those using formula feeding, who consistently followed a fixed feeding routine. When introducing solid foods, mothers from both groups often overlooked their babies' hunger and satiety cues, frequently pressuring their children to finish their entire plate. One cited reason for this was the challenge parents faced in identifying such cues. Arabic‐speaking mothers often supplemented with formula top‐ups after introducing solid foods, due to the belief that breast milk or solid foods alone might not sufficiently nourish their infants. Additionally, some Arabic‐speaking mothers used food‐based rewards to encourage eating. Mongolian mothers expressed a cultural preference for chubby babies, a potential reason why they may have been inclined to pressure‐feed their children. Moreover, both groups reported using digital devices to distract their children during meals. This study highlights the necessity of tailoring future resources and services related to responsive feeding practices to accommodate diverse literacy levels and cultural backgrounds.